An Ecological Study of a Universal Employee Depression Awareness and Stigma Reduction Intervention: “Right Direction” - Doty, Benjamin; Grzenda, Adrienne; Hwang, Seungyoung; Godar, Sean; Gruttadaro, Darcy; Hauge, Kimberly A.; Sherman, Bruce; Clarke, Diana E. (Frontiers in Psychiatry, 2021)
Objective: Right Direction (RD) was a component of a universal employee wellness program implemented in 2014 at Kent State University (KSU) to increase employees’ awareness of depression, reduce mental health stigma, and encourage help-seeking behaviors to promote mental health. We explored changes in mental health care utilization before and after implementation of RD. Methods: KSU Human Resources census and service use data were used to identify the study cohort and examine the study objectives. A pre-post design was used to explore changes in mental health utilization among KSU employees before and after RD. Three post-intervention periods were examined. A generalized linear mixed model approach was used for logistic regression analysis between each outcome of interest and intervention period, adjusted by age and sex. Logit differences were calculated for post-intervention periods compared to the pre-intervention period. Results: Compared to the pre-intervention period, the predicted proportion of employees seeking treatment for depression and anxiety increased in the first post-intervention period (OR=2.14, 95% Confidence Interval [CI] = 1.37-3.34), then declined. Outpatient psychiatric treatment utilization increased significantly in the first two post-intervention periods (OR =1.89, 95% CI = 1.23-2.89; OR=1.75, 95% CI=1.11-2.76). No difference was noted in inpatient psychiatric treatment utilization across post-intervention periods. Unlike prescription for anxiolytic prescriptions, receipt of antidepressant prescriptions increased in the second (OR=2.25, 95% CI=1.56-3.27) and third (OR=2.16, 95% CI=1.46-3.20) post-intervention periods. Conclusions: Effects of RD may be realized over the long-term with follow-up enhancements such as workshops/informational sessions on mindfulness, stress management, resiliency training, and self-acceptance.